Effect of Different Modes of Erbium: yttrium Aluminum Garnet Laser on Shear Bond Strength to Dentin - Kucukyilmaz, E.; Botsali, M. S.; Korkut, E.; Sener, Y.; Sari, T. (My University, 2017)
Objectives: The aim of this study was to evaluate the effect of different surface treatments on the shear bond strength (SBS) of resin composites to dentin using total etch dentin bonding adhesives. Materials and Methods: Sixty extracted human molars were flattened to obtain dentin surfaces. The samples were divided into three groups (n = 20): Group I: 37% phosphoric acid + optibond FL + resin composite; Group II: Erbium: yttrium aluminum garnet (Er: YAG) laser (medium short pulse [MSP] mode, 120 mJ/10 Hz) + optibond FL + resin composite; Group III: Er: YAG laser (quantum square pulse [QSP] mode, 120 mJ/10 Hz) + optibond FL + resin composite. After the specimens were prepared, the SBS test was performed at a crosshead speed of 0.5 mm/min. The fractured specimens were examined under a stereomicroscope to evaluate the fracture pattern. Statistical analyses were performed with one-way ANOVA and Tukey-s honestly significant difference tests. One sample of treated dentin surface from each group was sputter-coated with gold, and scanning electron microscope (SEM) images were captured. Results: Acid etching showed significantly higher SBS than the other groups (P 0.05). SEM images of the acid-etched dentin surface showed opened dentinal tubule with a regular surface, but Er: YAG MSP mode treated surface was irregular. The surface treated with Er: YAG QSP mode represented wide dentinal tubules with a clean and flat surface. Conclusion: Using different modes (MSP and QSP) of Er: YAG laser for dentin surface treatment before application of total etch adhesives is still not an sufficient alternative compared to acid etching.